Legitimizing Benefit Corporations: An Italian Perspective on Mandatory Non-Financial Reporting (European journal of volunteering and community-based projects, 2024)
Purpose: Analyze how Italian Benefit Corporation (BC) use their mandatory non-financial report (SIR) to enhance corporate legitimations and therefore comprehend if SIR is used in substantive or symbolic approach.Design/Method/Approach: The study analyzes Impact reports (SIRs) of 56 Italian Benefit Corporations (BCs), chosen from ORBIS database. The analysis is conducted through the lens of legitimacy theory and through a content analysis of SIR.Findings: the results revealed the presence of organizations which have not yet fully understood the importance of the accountability and communication processes in terms of sustainability, legitimation.Originality: This is an original contribution, that considers the new interconnection between mandatory non-financial reporting and hybrid organizations.Practical and social implication: The results could be useful for scholars, since they contribute to deepening the issue of mandatory non-financial reporting in hybrid organizations and its effects in terms of legitimacy, but also for practitioners and hybrid organizations in understanding the importance of materiality of disclosure and in structuring material reporting.